Adolescent Perspectives on HIV Prevention: A Descriptive Study of High School Students - Raihan, Fatwa Muhammad; Hernawaty, Taty; Kurniawan, Kurniawan (Indonesian Journal of Global Health Research, 2024)
The incidence of HIV in adolescents has increased. Teenagers who have high curiosity like to try new things and are driven by the progress of the times are vulnerable to promiscuity, so this makes teenagers vulnerable to the risk of contracting HIV. This vulnerability is to the Health Belief Model theory. This study aims to determine perceptions of HIV prevention at SMAN 1 Pangandaran. This research uses a quantitative descriptive method with a cross-sectional method. The population of this study was all students of SMAN 1 Pangandaran, totaling 1355 people. Sampling used the Stratified Random Sampling technique with a sample size of 104 people. Data were collected using The AIDS Health Belief Scale questionnaire (r0.52-0.93, (Cronbach alpha) a0.72). Data analysis uses descriptive statistics. Perception of susceptibility to HIV infection is in the medium range (57.7%), perception of the severity of HIV infection is in the high range (55.8%), perception of the benefits of HIV prevention is in the medium range (42.3%), and perception of barriers in HIV prevention is to the medium range (56.7%). The overall perception of students at SMAN 1 Pangandaran is good.